An imidazole functionalized porous organic polymer for the highly efficient extraction of uranium from aqueous solutions. (27th April 2022) - Zhang, Qinghua; Zeng, Kai; Wang, Changfu; Wei, Peng; Zhao, Xiaohong; Wu, Faming; Liu, Zhirong
Abstract : Solvothermal polymerization of a porous polymer functionalized with a high concentration of imidazole groups and its application in the efficient extraction of uranium from water. Abstract : With the development of nuclear power, extraction of uranium from aqueous solutions using imidazole functionalized sorbents is extremely important for environmental protection and the sustainable development of atomic power since imidazole shows high selectivity for uranium. However, the uranium extraction capability of imidazole is frequently constrained because of the comparatively low coordination affinity of nitrogen atoms towards uranium, which seriously inhibits the practical use. Herein, a novel imidazole functionalized porous organic polymer adsorbent P(DVB-VIM) was facilely developed by solvothermal polymerization of vinyl imidazole (VIM) and divinylbenzene (DVB). Surprisingly, the maximum adsorption capacity ( q max ) for uranium on P(DVB-VIM) was 689.6 mg g −1 with a good selectivity of 85.5% in aqueous solution containing 9 co-existing ions, suggesting that imidazole introduced by solvothermal polymerization not only demonstrated a high selectivity for uranium, but has a robust coordination affinity towards uranium. More importantly, the adsorbent could also be recycled for at least twenty cycles without any obvious decrease of its adsorption ability. The high adsorption efficiency for uranium was mainly attributed to the high content of accessible imidazole ligands, and increasing the concentration of imidazole would result in higher adsorption capacity, which was verified by the experimental results. Both XPS and DFT analysis confirmed that only the N atom in CN of imidazole took part in uranium coordination. The result from DFT also revealed that the optimized geometric structures of 1 : 2 of UO2 2+ with the two non-adjacent imidazole groups of the same polymer chain could describe the interaction of uranium with P(DVB-VIM). This work provided a feasible tactic to develop adsorbents with excellent uranium extraction efficiency for environmental protection and sustainable development of nuclear energy.